Mesopotamian Coronation and Accession Rites in the Neo-Sumerian and Early Old Babylonian Periods, ca. 2100-1800 B.C. - Wilkinson, Richard Herbert (1986)
Ph.D. Dissertation; Adviser: Daniel D. Reisman.Order No. DA8700599. Cf. DissAbstr 47/09 (March 1987) 3532-A.